Relationship between Anxiety Level and Vital Signs of Pneumonia Patients in Hospital - Ayatulloh, Daviq; Priyantini, Diah; Fuad, Abdullah; Fiani, Putri Ohkta; Kiptiyah, Mariyatul; Nurfiyatul Jannah, Gangga Kristin (Jurnal Keperawatan Muhammadiyah, 2025)
Pneumonia is one of the acute respiratory tract infections that is still a serious and complex global health problem, with a very significant impact on public health worldwide. The purpose of this study was to analyze the relationship between anxiety levels and vital signs in hospitalized pneumonia patients. This study used an observational analytical research design with a cross-sectional approach with 64 respondents were recruited using convenience sampling techniques. The independent variable of the study was anxiety level and the dependent variable was vital signs (blood pressure, pulse, respiration, and temperature). The research instrument used was the Hamilton Anxiety Rating Scale (HARS) Questionnaire to measure anxiety levels and the dependent variable was measured using the Vital Signs Observation Sheet, Digital Tensimeter and Digital Thermometer. Data Analysis Data were analyzed using the Spearman or Pearson correlation test (according to data normality) with a confidence level of 95% (α = 0.05). Vital signs of pneumonia patients showed that 28.13% of patients were not anxious and had normal blood pressure, 25.00% of patients had normal respiration rate, 21.88% showed normal pulse rate and 23.44% showed normal oxygen saturation. High anxiety levels showed that 25.00% of patients had abnormal blood pressure, 25.00% of patients had abnormal respiration rate, 28.13% showed abnormal pulse rate and 23.44% of patients had abnormal oxygen saturation. The results of the study showed that anxiety had a significant relationship with blood pressure, pulse rate, respiration rate, and oxygen saturation with a p value <0.05.